Facial Nerve Outcome after Vestibular Schwannoma Surgery: Our Experience - Rinaldi, Vittorio (Thieme Medical Publishers, 2012)
In this study we evaluate the postoperative facial nerve function after vestibular schwannoma (VS) surgery and analyze the factors that cause it. We included 97 consecutive patients undergoing surgical excision of sporadic unilateral VS. Patient and tumor characteristics, surgical approaches, facial nerve function, extent of tumor removal, perioperative complications are all analyzed through standardized systems. Four different surgical approaches are used: translabyrinthine, retrolabyrinthine, retrosigmoid, and middle cranial fossa. Anatomic preservation of the facial nerve is achieved in 97% of patients. The incidence of postoperative facial palsy is found to be statistically correlated to tumor size, but not to the surgical approach used and to extent of tumor penetration in the internal auditory canal. A significant improvement of the short-term facial nerve outcome is detected in patients undergone simultaneous intraoperative electromyography (EMG) and pneumatic facial nerve monitoring. Complete tumor excision is achieved in 94% of cases. Complication rates are excellent and no deaths are reported. Short- and long-term facial nerve outcome is good and comparable with those of other series reported in literature. In VS surgery both EMG and pneumatic facial nerve monitors should be simultaneously used. Further investigations are desirable to improve the facial outcome respecting the oncological radicality.